MANAJEMEN KELAS DALAM MEWUJUDKAN PEMBELAJARAN BERDIFERENSIASI BAIK DI MTS AN-NUR PELOPOR DAN MTS AN-NUUR GUPPI LAMPUNG TENGAH - Yosi Alwi; Oki Dermawan; Sovia Mas Ayu (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Classroom management is an effort made by an educator to plan, organize, direct, and implement a program of monitoring activities in the classroom, so that the learning process can be arranged systematically, effectively and efficiently. Differentiated learning is an effort to adjust the learning process by providing various ways through differentiation of content, process and product as well as the initial environment and initial assessment to meet the individual learning needs of each student. This study aims to analyze classroom management in realizing differentiated learning both in MTS An-nur Pelopor and MTS An-nuur GUPPI Lampung Tengah. This study analyzes and analyzes the stages of planning, organizing, directing, and supervision. The type of research used in the effort to collect and the author uses the observation, interview, and documentation methods. While the nature of this research includes qualitative descriptive research. This qualitative method uses a type of case study research, namely a case study. Data analysis in this study used a continuous procedure, starting from the beginning of the data collected until the end of the researcher saw data reduction, displayed data and drew conclusions. The results of the study showed, (1) Planning: The second madrasah showed challenges and differences in the implementation of differentiated learning. Teachers tried to fulfill aspects of planning such as determining what would happen, when and how to do it, limiting targets, developing alternative actions, and collecting and analyzing information and preparing and communicating plans and decisions. (2) Organization: MTS An-nur Pelopor and MTS An-nuur GUPPI Lampung Tengah showed good efforts in organizing resources and structures, although there were differences in the level of training and understanding of the Merdeka Curriculum. Teachers tried to optimize facilities, group the workforce effectively, and form a clear coordination structure. (3) Direction: In the direction stage, despite facing challenges in compiling time and cost frameworks and providing specific instructions, teachers in both madrasahs showed dedication in implementing the learning plan. They actively provide guidance, motivation, and supervision to students, reflecting a commitment to student development. (4) Supervision: The supervision process in both madrasahs is carried out proactively by implementing continuous evaluation and handling appropriate obstacles. Teachers use comprehensive assessment and feedback to improve the quality of learning and handle deviations.